The relationship between knowledge about breast cancer and self-examination behavior in adolescents - Nurlaela Ardillah; Sri Riyana; Dwi Sri Handayani (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast cancer at the end of 2020, 7.8 million women were still alive and had been diagnosed with breast cancer in the past five years, making breast cancer the most common type of cancer worldwide, with the highest prevalence rate in the Special Region of Yogyakarta (2.4% or 4,325 cases). Adolescents' awareness of breast cancer plays a crucial role in their early screening through breast self-examination (BSE). Early detection can reduce breast cancer deaths by up to 20%. Purpose: to determine the relationship between knowledge about breast cancer and BSE behavior in adolescents. Method: This study used a quantitative method with a correlational design with a cross-sectional approach. The sample was taken using a probability sampling technique with a population of 60 adolescents and a sample of 54 respondents in grade 12. The research instruments used were a breast cancer knowledge questionnaire and a BSE behavior questionnaire adopted from research with a reliability value of 0.598 for the breast cancer knowledge questionnaire and 0.694 for the BSE behavior questionnaire so that the questionnaire was declared valid. The results were analyzed using the Spearman sign rank test. Results: The results obtained were insufficient knowledge of 72.2%, sufficient knowledge of 22.2%, and good knowledge of 5.6%. Adequate behavior of 5.6%, and poor behavior of 94.4%. The results of the relationship obtained using the Spearman rank test obtained the value of breast cancer knowledge and awareness behavior of p 0.004 <0.05. Conclusion: So that there is a significant relationship between knowledge about breast cancer and BSE behavior in adolescents.